2011
DOI: 10.1596/978-0-8213-8538-8
|View full text |Cite
|
Sign up to set email alerts
|

Health, Nutrition, and Population in Madagascar, 2000-09

Abstract: World Bank Working Papers are published to communicate the results of the Bank's work to the development community with the least possible delay. The manuscript of this paper therefore has not been prepared in accordance with the procedures appropriate to formally-edited texts. Some sources cited in this paper may be informal documents that are not readily available. This volume is a product of the staff of the International Bank for Reconstruction and Development/The World Bank. The fi ndings, interpretations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 2 publications
0
13
1
Order By: Relevance
“…2 This condition has been attributed in part to the inadequate access to assisted deliveries but also to the insufficient quality of antenatal care (ANC). 3 In 2018, the latest Demographic and Health Surveys for Madagascar reported that only 51% of women attended four or more ANC consultations. 4 This is especially important as WHO recommended in 2016 a minimum of eight antenatal care contacts to reduce perinatal mortality and improve women's experience of care.…”
Section: Introductionmentioning
confidence: 99%
“…2 This condition has been attributed in part to the inadequate access to assisted deliveries but also to the insufficient quality of antenatal care (ANC). 3 In 2018, the latest Demographic and Health Surveys for Madagascar reported that only 51% of women attended four or more ANC consultations. 4 This is especially important as WHO recommended in 2016 a minimum of eight antenatal care contacts to reduce perinatal mortality and improve women's experience of care.…”
Section: Introductionmentioning
confidence: 99%
“…We analyzed data from a study cohort established in 2004 when children were 0 to 3 years old, during an evaluation of a national nutrition program in Madagascar aimed at reducing the high prevalence of malnutrition in the country. First implemented in 1999 by the National Office of Nutrition (ONN), the ongoing program included over 5,550 sites with coverage of approximately 1.1 million children [ 30 ]. For the study, children living in 150 low-income communities from all six provinces in Madagascar were administered a battery of tests in 2007 (when children were 3 to 6 years) and again in 2011 (when they were 7 to 10 years).…”
Section: Methodsmentioning
confidence: 99%
“…However, some estimates put abortion rates at 1 per 10 live births. Abortion complications are one of the major contributors to maternal death in the country (Sharp et al, 2011). 2 In developing countries, empirical evidence has shown a positive association between maternal education and children's health (Strauss and Thomas, 1995); however, causality has been less empirically tested with the exception of few studies (Güneş, 2015;Behrman et.…”
Section: Introductionmentioning
confidence: 99%
“…There is no sexual curriculum in the education system. 6 The low HIV/AIDS prevalence in Madagascar despite a high prevalence of STIs (one of the highest in SubSaharan Africa), relatively high rate of sexual partner change, and early sexual initiation is considered an anomaly, but still a threat for public health (Sharp and Kruse, 2011). 6 and preferences over family planning. We do not find any evidence of non-random program placement in any of these exercises.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation